Answer:
[tex] y-b= m (x-a)[/tex]
For this case we know that m =-4 represent the slope. And with the point given (4,-9) we can find the values of a and b and we got:
[tex] a=4, b=-9[/tex]
And replacing we got:
[tex] y-(-9) =-4(x-4)[/tex]
[tex] y+9 =-4(x-4)[/tex]
And the best solution would be:
A. y + 9 = -4(x-4)
Step-by-step explanation:
For this case we need to remember that the general expression for the slope line is given by:
[tex] y-b= m (x-a)[/tex]
For this case we know that m =-4 represent the slope. And with the point given (4,-9) we can find the values of a and b and we got:
[tex] a=4, b=-9[/tex]
And replacing we got:
[tex] y-(-9) =-4(x-4)[/tex]
[tex] y+9 =-4(x-4)[/tex]
And the best solution would be:
A. y + 9 = -4(x-4)